Termination of the Administered Account for Liberia. (Policy Papers; Policy Paper ;, 2013)
On March 14, 2008 the Fund established the Administered Account for Liberia ('Liberia Administered Account' or LAA) to facilitate fundraising for, and delivery of, debt relief to Liberia with respect to obligations owed to the Fund. Specifically, the account was intended to: (i) receive resources contributed for the financing of the IMF's share of debt relief to Liberia; and (ii) use these resources, as provided for in the Instrument to establish the LAA, to make contributions in the context of debt relief to Liberia under the Heavily Indebted Poor Country (HIPC) Initiative, and to deliver 'beyond-HIPC' debt relief to Liberia (Attachment). As stipulated in the Instrument (paragraph 10(a)), the LAA shall remain in effect for as long as necessary, in the judgment of the Fund, to conduct and wind up the business of the account. Following Liberia's successful achievement of the HIPC completion point in June 2010 and the full delivery of 'beyond-HIPC' debt relief, which exhausted the balances in the account, the LAA can be terminated as it has no pending business.